Liberalism and capitalism - Miller, Fred D., Jr. , 1944-; Paul, Ellen Frankel; Paul, Jeffrey (Cambridge University Press, 2011)
Political philosophers, theorists and historians address what are the core values of liberalism and how can they best be promoted?